Does Form-focused Instruction Affect L Learners' Performance?: Insights from Cognitive Psychology and SLA Pesearch. - El-dali, Hosni M. (Arab Journal for the Humanities)
Recent years have seen a growing concern with the role of conscious process in Second Language Acquisition (SLA). This concern is frequently centered on the "Noticing Hypothesis" of Richard Schmidt (1990; 1993a; 1994; 1995a; 1995b; 2001; Schmidt and Frota, 1986). This study, then, examines Schmidt's hypothesis that L learners must consciously notice the grammatical form of their input in order to acquire grammar. Fifteen subjects participated in this study. They were asked, first, to write an essay on the value of learning English. Second all subjects performed on two correction tasks; one was unfocused and the other was focused. Finally, each student was interviewed to explain his/her performance in the three tasks. The data analysis had a quantitative part which consisted of statistical comparison of the number of errors in the composition, unfocussed correction and focused correction tasks (by means of one-way ANOVA). It also had a qualitative part which was an analysis of each student's conception of the grammatical rules that were violated in order to explain any discrepancies between their performances in the three tasks. This study, first, demonstrates that the deficiency in L learners' knowledge results in inaccurate composition writing and unsuccessful correction of errors even if their attention was drawn to these errors, Second, it offers another interpretation for the noticeable discrepancies in the subjects' performance. Such an interpretation is mainly based on the argument that composing in English is a multidimensional activity which requires L learners to do more than one thing simultaneously. Third, it shows that our students' failure to perform systematically may be due, sometimes, to cognitive deficiency. Accordingly, this study supports the view that language acquisition may not be fully understood without addressing the interaction between language and cognition. Fourth, this study shows that although 'noticing' or 'conscious awareness' may have some positive effect on L learners' performance; this effect, however, is constrained by two important factors: (1) learners' overall linguistic competence and (2) the nature of the task; that is, whether it requires controlled or automatic processing of information.